2017
DOI: 10.1097/mib.0000000000001132
|View full text |Cite
|
Sign up to set email alerts
|

Single Delivery of High-Diversity Fecal Microbiota Preparation by Colonoscopy Is Safe and Effective in Increasing Microbial Diversity in Active Ulcerative Colitis

Abstract: Background: Recent trials suggest fecal microbiota transplantation (FMT) with repeated enemas and high diversity FMT donors is a promising treatment to induce remission in ulcerative colitis (UC). Methods: We designed a prospective, open-label pilot study to assess the safety, clinical efficacy, and microbial engraftment of single FMT delivery by colonoscopy for active UC using a two donor fecal microbiota preparation (FMP). Safety and clinical endpoints of response, remission, and mucosal healing at week 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 22 publications
2
92
1
1
Order By: Relevance
“…Despite the small sample size, the results suggest that donor FMT engraftment in this patient group is surprisingly low despite a combined endoscopic and oral high-intensity FMT approach, which is considered one of the factors of success for FMT in patients with UC [14]. In contrast, engraftment of FMT in patients with a preserved colon in FMT trials for recurrent C. difficile infection and UC is at least 80% [15, 16]. Also, as shown in patients with UC undergoing FMT, the microbiome of recipients after transplant is more similar to the donor FMP than the pretransplant recipient sample engraftment, suggesting that FMT engraftment is a prerequisite for therapeutic success [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the small sample size, the results suggest that donor FMT engraftment in this patient group is surprisingly low despite a combined endoscopic and oral high-intensity FMT approach, which is considered one of the factors of success for FMT in patients with UC [14]. In contrast, engraftment of FMT in patients with a preserved colon in FMT trials for recurrent C. difficile infection and UC is at least 80% [15, 16]. Also, as shown in patients with UC undergoing FMT, the microbiome of recipients after transplant is more similar to the donor FMP than the pretransplant recipient sample engraftment, suggesting that FMT engraftment is a prerequisite for therapeutic success [16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, engraftment of FMT in patients with a preserved colon in FMT trials for recurrent C. difficile infection and UC is at least 80% [15, 16]. Also, as shown in patients with UC undergoing FMT, the microbiome of recipients after transplant is more similar to the donor FMP than the pretransplant recipient sample engraftment, suggesting that FMT engraftment is a prerequisite for therapeutic success [16]. The reason for the low engraftment in our study could be due to several factors, including donor selection, the dose and frequency of FMT, and the pouch microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…However, over time, the abundance of flora from the same donor varies significantly and, therefore, extensive microflora provided by multiple donors could effectively treat recurrent UC. Another study reported that, in patients with active UC, the high diversity of two‐donor FMT administered through a colonoscopy appears to be a safe and effective strategy for increasing fecal microbial diversity with an aim of clinical remission …”
Section: Therapeutic Strategy Of Fmt In Uc and Controversymentioning
confidence: 99%
“…The concept that donor stool characteristics may influence FMT efficacy has been recognized in inflammatory bowel disease . Bajaj et al carried forward this novel concept by utilizing donor stool enriched with microbial taxa found to be beneficial in cross‐sectional HE studies .…”
Section: Is There Evidence For Rational Donor Selection?mentioning
confidence: 99%
“…The concept that donor stool characteristics may influence FMT efficacy has been recognized in inflammatory bowel disease. (8) Bajaj et al carried forward this novel concept by utilizing donor stool enriched with microbial taxa found to be beneficial in cross-sectional HE studies. (2) Although an excellent starting point for targeted donor selection, this "one-size-fits-all" approach to donor selection will likely benefit from further refinement given that: (1) not all patients with the same disease have similar microbial profiles (9) and (2) our current understanding of "beneficial" taxa from cross-sectional HE studies is based on association rather than causation.…”
Section: Is There Evidence For Rational Donor Selection?mentioning
confidence: 99%